Pronunciation fundamentals : evidence-based perspectives for L2 teaching and research - Derwing, Tracey M; Munro, Murray J (Language Learning & Language Teaching, 2015)
The emergence of empirical approaches to L2 pronunciation research and teaching is a powerful fourth wave in the history of the field. Authored by two leading proponents of evidence-based instruction, this volume surveys both foundational and cutting-edge empirical work and pinpoints its ramifications for pedagogy. The authors begin by tracing the history of pronunciation instruction and explicating L2 phonetic learning processes. Subsequent chapters explore the themes, strengths, and ethical problems of the field through the lens of the intelligibility principle. The importance of error gravity, and the need for assessment and individualized instruction are highlighted, and the role of L2 accents in social contexts is probed. Material readily available elsewhere has been omitted in favour of an emphasis on the how, why, and when of pronunciation instruction. Anyone with an interest in L2 pronunciation-especially graduate students, language teachers, and experienced researchers-will find much value in this indispensible resource.